2011
DOI: 10.1007/s00520-011-1101-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of patients with laryngectomies as they reintegrate into their community

Abstract: Patients with laryngectomies face major changes in lifestyle related to altered airway, loss of voice, body image concerns, and challenges with eating. Support of family, friends, and health care professionals is critical for successful transition during this stressful period. Instant messaging, email, Web-based support groups, and video messaging can contribute to a great improvement in communication and engagement for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 25 publications
2
52
0
Order By: Relevance
“…In line with others [1,2] , our study revealed that patients experience challenges in their rehabilitation process related to physical changes, in relation to psychological concerns [30] , and with regard to integrating their new situation into their everyday life. Because of its low priority, 'Information how to manage emotions' was not included.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In line with others [1,2] , our study revealed that patients experience challenges in their rehabilitation process related to physical changes, in relation to psychological concerns [30] , and with regard to integrating their new situation into their everyday life. Because of its low priority, 'Information how to manage emotions' was not included.…”
Section: Discussionsupporting
confidence: 58%
“…This approach resulted in more insight into patients' self-care needs and in high levels of satisfaction among patients and speech therapists in the usability tests. While a couple of (Web-based) interventions to promote self-management in head and neck cancer patients have been developed [27,28] , 'In Tune without Cords' is the first Webbased intervention to support laryngectomees, hereby fulfilling the reported need for a Web-based self-care program [2] . Affecting motivation, skill building, and behavioral change demands instructional strategies that move beyond text on a screen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, TL is most commonly reserved for those who fail chemoradiation, have extensive disease with contiguous spread or cartilage invasion, or present with a nonfunctional larynx . Despite the accepted indications, TL is known to negatively impact patient quality of life in several domains including speech, eating, aesthetics, and social interactions …”
Section: Introductionmentioning
confidence: 99%